PAI TEACHER PERFORMANCE IN IMPLEMENTING AQIDAH LOWER CLASS STUDENTS IN SDN GUGUS V KECAMATAN LUBUK BASUNG KABUPATEN AGAM - ratna dayerni (Program Pascasarjana UMSB, 2022)
This study aims to determine and discuss the performance of PAI teachers in instilling the aqidah of low-grade students in SDN Gugus V, Lubuk Basung sub-district, Agam Regency. This research is a qualitative research, while the data collection uses the observation method, interview method and documentation method. This research was carried out in Cluster V which consisted of four elementary schools: 1) SD Negeri 52 Sago, Lubuk Basung District, 2) SD Negeri 24 Sungai Jaring, Lubuk Basung District, and 3) SD Negeri 50 Padang Tongga, Lubuk Basung District and 4) SD Negeri 44 Padang Mardani, Lubuk Basung District. This study concludes that the performance of PAI teachers in instilling students' aqidah is good enough to make students a better person than before, this cannot be separated from the cooperation of the teacher and the principal. The results of the study revealed that: 1) The psychological characteristics of the low-grade students themselves who like to play and actively move, the teacher instills the students' faith in Allah SWT by inviting students to directly observe His existing creations and provide opportunities for students to ask questions about what He has created. he observed. And low grade students who have group psychology are taught to love each other among group members, which is an imitation of the merciful nature of Allah SWT. 2) The psychological characteristics of low-grade students themselves who like to play and actively move, the teacher explains or inculcates the student's belief in God and angels by inviting students to observe directly some events that occur which are the work of angels, such as inviting students to see people die. And students who have psychology demonstrating something, then students are asked to demonstrate the nature of angels who are always obedient and obedient to Allah SWT. 3) The psychological characteristics of low-grade students themselves who like to play and actively move, the teacher explains or inculcates the student's aqidah to the final day by inviting students to watch a video about the Day of Judgment presented by the teacher. So with the character who easily remembers what was conveyed, students will really remember how terrible the Day of Judgment was.